UPAYA MENINGKATKAN KEMAMPUAN KOGNITIF MELALUI KEGIATAN MENCAMPUR WARNA DALAM PERCOBAAN SAINS - Amami, Eneng Sri Susilawati, Subhan (JURNAL PENDIDIKAN DAN PENELITIAN SERUMPUN MENGAJAR, 2024)
This research aims to enhance cognitive abilities through colour-mixing activities in science experiments. The research method used in this study is the Class Action Research (PTK) method which consists of two cycles and each cycle has three meetings. The subject of this study, which is the age of 5-6 years in PAUD Bunda Pertiwi Prefecture of Tanara. Research data collection techniques, that is, through observation, and documentation. The results of the above research and discussion can be concluded from the existence of the development of the pupils which in the preliminary survey in knowing pupils who reached the standard of development of research very well there were only 2 children of all pupils that amounted to 12 pupils. Then in cycle 1 of meetings 1, the child with excellent cognitive abilities increased to 3 children, and in cyclus 1 of meeting 2 increased again to 5 children. Then in the cycle 2 of meeting 1 the child who has excellent cognitive abilities grew to 6 children; and in the second cycle of Meeting 2 increases to 8 children and has reached the established standard of evaluation.